Studi Komparatif Konstitusi di Indonesia dan Timor Leste : Analisis Aspek Inherent, Konstitusionalisme dan Pemilihan Umum Presiden - Fauziyah, Qothrunnada uni (Jurnal Konstitusi & Demokrasi, 2024)
A comparison of the constitutions between Indonesia and East Timor provides an interesting insight into how the two countries, which have different historical and cultural backgrounds, formulate their legal and political frameworks. Indonesia, as a country that has been independent since 1945, has a constitution that has undergone several amendments and changes along with political and social developments. On the other hand, East Timor, which gained independence in 2002 after decades of conflict and colonization, 24 years of integration with the Republic of Indonesia and has a newer Constitution and is still in the early stages of development. Another important aspect that is interesting to analyze is related to the presidential election. Indonesia, since the amendment of the 1945 Constitution, applies the presidential election system directly by the people, with a maximum limit of two terms of office. In East Timor, the people voted in a presidential election that was seen as a test of the country's democracy. Although the president's authority is very limited and tends to be a ceremonial position, East Timor's presidential election remains a very important and decisive event for the young country. The method used in this study is juridical normative approach to legislation (statute approach), historical approach (historical approach) and conceptual approach (conceptual approach). A comparative study of the constitutions of Indonesia and East Timor, focusing on inherent aspects, constitutionalism and presidential elections, provides a rich overview of the constitutional dynamics in two major countries with different historical and socio-cultural backgrounds. Thus we can draw important conclusions for the development of a better theory and practice of constitutionalism later. Keywords : Constitution, Inherent Aspects, Presidential Election, Indonesia, Timor-Leste